2013
DOI: 10.1088/0963-0252/22/6/065015
|View full text |Cite
|
Sign up to set email alerts
|

End-boundary sheath potential, electron and ion energy distribution in the low-pressure non-ambipolar electron plasma

Abstract: The end-boundary floating-surface sheath potential, electron and ion energy distribution functions (EEDf , IEDf ) in the low-pressure non-ambipolar electron plasma (NEP) are investigated. The NEP is heated by an electron beam extracted from an inductively coupled electron-source plasma (ICP) through a dielectric injector by an accelerator located inside the NEP. This plasma's EEDf has a Maxwellian bulk followed by a broad energy continuum connecting to the most energetic group with energies around the beam ene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
8
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 37 publications
0
8
0
Order By: Relevance
“…A large amount of research on physics and applications of beam plasma produced by an energetic (several keV) cylindrical or sheetlike magnetically-confined electron beams formed by plasma-cathode electron sources at much higher gas pressures of up to tens of Pa, have been performed by the research group of US Naval Research Laboratory [12][13][14][15], which demonstrated that such beam plasma has typically low (<1 eV) electron temperature due to electrons cooling in collisions with gas atoms and molecules [12,13], and employed this plasma for effective nitriding [14] and atomicprecise etching [15,16]. Chen et al [17] have investigated 80-600 eV dc electron beam injection in cylindrical volume having large positive potential with a floating dielectric end plate, at N 2 or Ar pressure of 0.1-0.4 Pa; authors demonstrated that energy of ions, incident to end plate, can be nearly mono-energetic, controllable by e-beam accelerating voltage, and at such low pressures, e-beam energy dissipation due to collective interaction prevails over dissipation in collisions with gas.…”
Section: Introductionmentioning
confidence: 99%
“…A large amount of research on physics and applications of beam plasma produced by an energetic (several keV) cylindrical or sheetlike magnetically-confined electron beams formed by plasma-cathode electron sources at much higher gas pressures of up to tens of Pa, have been performed by the research group of US Naval Research Laboratory [12][13][14][15], which demonstrated that such beam plasma has typically low (<1 eV) electron temperature due to electrons cooling in collisions with gas atoms and molecules [12,13], and employed this plasma for effective nitriding [14] and atomicprecise etching [15,16]. Chen et al [17] have investigated 80-600 eV dc electron beam injection in cylindrical volume having large positive potential with a floating dielectric end plate, at N 2 or Ar pressure of 0.1-0.4 Pa; authors demonstrated that energy of ions, incident to end plate, can be nearly mono-energetic, controllable by e-beam accelerating voltage, and at such low pressures, e-beam energy dissipation due to collective interaction prevails over dissipation in collisions with gas.…”
Section: Introductionmentioning
confidence: 99%
“…To further decrease ion energies, different alternative approaches have been proposed. One of the possible methods is the application of a nonselfsustained low-pressure rf plasma with additional ionization by an electron beam (EB) [18][19][20][21][22][23][24][25]. There are few results on the processing of materials in such plasma, for example, silicon [18] or graphene [26], which is easily damaged in conventional rf discharges.…”
Section: Introductionmentioning
confidence: 99%
“…In [24], layerby-layer etching of p-Si at ε i ∼ 25-50 eV using a cycling process (cycling of gas and EB, radical source power), as well as continuous etching of epi-grown µ-Si in Cl 2 -based plasmas, are demonstrated. Various EB sources and discharge configurations have been applied: a cold cathode electron gun source with single frequency rf plasma in [18,23], a hollow cathode EB source [19,20,26], an electron source based on ICP plasma [21] and an EB source together with an additional ICP radical source [24,25].…”
Section: Introductionmentioning
confidence: 99%
“…This is especially important for advanced plasma processing applications in order to produce high-aspect ratio nano-features of electronic devices. [14,15] One way to control the beam energy deposition in plasma is by profiling the background plasma density. [6] Conditions favorable for development of the beam-plasma instabilities depend on parameters such as the beam and plasma densities, plasma temperature, and plasma density gradients.…”
Section: Introductionmentioning
confidence: 99%